Viscosity measurements of 1-ethyl-3-methylimidazolium trifluoromethanesulfonate (EMIM OTf) at high pressures using the vibrating wire technique - Sequeira, Maria Carolina (2022)
The goal of the present work is to contribute to the characterization of ionic liquids by measuring their viscosity at high pressures. As 1-ethyl-3-methylimidazolium trifluoromethanesulfonate (EMIM OTf) has been used as a solvent in CO2 capture processes, the temperature and pressure ranges of the measurements cover the intervals used in those processes. Measurements of the viscosity of EMIM OTf along five isotherms in the range (298–358) K and at pressures up to 50 MPa, have been performed using the vibrating wire technique in the forced mode of operation. As far as the authors are aware, these are the first measurements of this ionic liquid at pressures higher than 0.1 MPa, to be published. The viscosity results were correlated with the molar volume, using a modified hard-spheres model. The root mean square (σ) deviation of the data from the correlation is less than 0.5% The expanded uncertainty of the present viscosity data is estimated as ±2.0% at a 95% confidence level. As a complement, the pressure-viscosity coefficient has been calculated within the temperature range of the present results. Previous studies of the influence of the electric conductivity of ionic liquids, including EMIM OTf, in the vibrating wire method, have been taken into account for the present work. Complementary measurements of the density have been performed along seven isotherms in the temperature range from (298–363) K and pressures from (0.1–70) MPa. The density measurements were carried out with an Anton Paar vibrating U-tube densimeter and the raw data were corrected for viscosity effects. The density results were correlated with the temperature and pressure using a modified Tait equation. The expanded uncertainty of the present density data is estimated as ±0.2% at a 95% confidence level.